PENGGUNAAN ENZIM SELULASE DALAM RANSUM SEBAGAI UPAYA PENINGKATAN PENDAPATAN PETERNAK - Priadi, Gogok (Jurnal Bestari, 1992)
This research finding was decided as the first winner of the scientific research which sponsored by KOPERTIS wilayah VII, East Java. The researcher is the student of Animai Husbandry Faculty, University of Muhammadiyah Malang.